ZAKAT FITRAH DISTRIBUTION THROUGH THE LENS OF ZAKAT MANAGEMENT: A CASE STUDY OF ZAKAT FITRAH DISTRIBUTION AT MASJID ANSARIAH SEBAKUNG - Intan Kelana; Said Muhammad Rahimin; Kartubi (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to examine the mechanism of zakat fitrah distribution at Masjid Ansariah Sebakung and to analyze the extent to which the distribution practice aligns with the ideal principles of zakat management. This research employed a qualitative approach with a single case study design. Data were collected through in-depth interviews with mosque administrators, direct observation of the distribution process, and documentation review of zakat records. Data analysis followed the interactive model proposed by Miles et al., encompassing data condensation, data display, and conclusion drawing, while data validity was ensured through source triangulation. The findings reveal that the distribution mechanism operates through structured stages, including committee formation, collection, recording, beneficiary identification, and timely disbursement prior to Eid prayer, supported by strong social capital within the community. However, the practice has not fully met the ideal standards of zakat management, particularly in terms of formal accountability reporting, standardized beneficiary verification, and measurable impact evaluation. This study concludes that technical success in zakat distribution does not automatically reflect comprehensive zakat management, and that context-sensitive operational guidelines for mosque-based zakat institutions are urgently needed. These findings carry significant implications for the achievement of the Sustainable Development Goals, particularly SDG 1 on poverty eradication and SDG 10 on reduced inequalities.